Loop-mediated isothermal amplification (LAMP) as a promising point-of-care diagnostic strategy in avian virus research - Padzil, Faiz; Abdul Razak, Mariatulqabtiah; Tan, Wen Siang; Ho, Kok Lian; Mat Isa, Nurulfiza; Lau, Han Yih; Abu, Jalila; Chuang, Kuo-Pin (MDPI AG, 2021)
Over the years, development of molecular diagnostics has evolved significantly in the detection of pathogens within humans and their surroundings. Researchers have discovered new species and strains of viruses, while mitigating the viral infections that occur, owing to the accessibility of nucleic acid screening methods such as polymerase chain reaction (PCR), quantitative (real-time) polymerase chain reaction (qPCR) and reverse-transcription qPCR (RT-qPCR). While such molecular detection methods are widely utilized as the benchmark, the invention of isothermal amplifications has also emerged as a reliable tool to improvise on-field diagnosis without dependence on thermocyclers. Among the established isothermal amplification technologies are loop-mediated isothermal amplification (LAMP), recombinant polymerase amplification (RPA), strand displacement activity (SDA), nucleic acid sequence-based amplification (NASBA), helicase-dependent amplification (HDA) and rolling circle amplification (RCA). This review highlights the past research on and future prospects of LAMP, its principles and applications as a promising point-of-care diagnostic method against avian viruses.